The closure of a model category (1977)
The concept of model category is due to Quillen [1]. It represents an axiomatic aproach to homotopy in which not only homotopy itself but also several of the concepts of Algebraic Topology are developed, such as fibrations, loop and suspension functors, homology and homotopy sequences, among others. Thus in order to precise the aims of this paper we first give the definition of a model category.